2022
DOI: 10.3389/fphys.2022.831372
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arm-Crank Exercise on Fitness and Health in Adults With Chronic Spinal Cord Injury: A Systematic Review

Abstract: Individuals with spinal cord injury (SCI) may benefit less from exercise training due to consequences of their injury, leading to lower cardiorespiratory fitness and higher risks of developing cardiovascular diseases. Arm-crank exercise (ACE) is the most common form of volitional aerobic exercise used by people with SCI outside a hospital. However, evidence regarding the specific effects of ACE alone on fitness and health in adults with SCI is currently lacking. Hence, this review aimed to determine the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 78 publications
(239 reference statements)
0
9
0
Order By: Relevance
“…This review revealed there were no significant subgroup differences between exercise modalities in AV ̇O2peak or RV ̇O2peak, indicating that improvements can be gained from any form of exercise intervention. The change in RV ̇O2peak in the current review (21%) is equivalent to the average 21% improvement reported in a recent systematic review on the effects of ACE in chronic SCI [107]. Whilst the current review did not exclusively investigate ACE, it is evident that aerobic, volitional upper-body Several studies directly compared the effects of specific exercise modalities on the change in CRF [54,76,114].…”
Section: Exercise Modalitymentioning
confidence: 57%
See 2 more Smart Citations
“…This review revealed there were no significant subgroup differences between exercise modalities in AV ̇O2peak or RV ̇O2peak, indicating that improvements can be gained from any form of exercise intervention. The change in RV ̇O2peak in the current review (21%) is equivalent to the average 21% improvement reported in a recent systematic review on the effects of ACE in chronic SCI [107]. Whilst the current review did not exclusively investigate ACE, it is evident that aerobic, volitional upper-body Several studies directly compared the effects of specific exercise modalities on the change in CRF [54,76,114].…”
Section: Exercise Modalitymentioning
confidence: 57%
“…Despite a number of recent reviews summarising the effects of specific exercise modalities on the change in CRF following SCI, including aerobic ACE [107], FES-cycling [39], and aerobic plus muscle strength training (mixed multimodal) interventions [108], this meta-analysis is the first to directly compare the effects of a wide range of exercise modalities on the change in CRF in individuals with SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Accordingly, moderate-tovigorous-intensity aerobic exercise is highly encouraged in individuals with SCI to help reduce the risk of CVD. 6 Upper-body aerobic exercise, such as arm-cycle ergometer training (ACET), is the most common modality to improve cardiometabolic health in this population; 7,8 however, some studies have shown that passive lower limb exercise such as body-weight-supported treadmill training (BWSTT) are well tolerated and have the potential to improve cardiovascular function in individuals with SCI. [9][10][11] While there is some evidence that BWSTT can improve resting cardiovascular function in SCI, little is known about the effects of BWSTT, or indeed ACET, on cardiac autonomic responses to physiological stressors such as an orthostatic challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Arm cycling exercise is a form of volitional exercise commonly used by individuals with SCI for cardiorespiratory fitness 27 . The exercise is simple and can be performed outside a clinical setting by individuals without supervision from professionals, positing an opportunity to overcome the barriers of current approaches for trunk rehabilitation.…”
Section: Introductionmentioning
confidence: 99%